Pengaruh Penggunaan Gadget Terhadap Konsentrasi Belajar Peserta Didik di SD 101 Panyabungan - Nur Hatikah (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2026)
This study aims to explore the effect of gadget use on students' learning concentration at SD 101 Panyabungan. In this study, gadgets are defined as portable electronic devices such as smartphones, tablets, or similar devices used by students in their daily lives. The research method used a quantitative approach with a survey of a number of students, teachers, and parents as respondents. The results showed that the intensity and type of gadget use had a negative correlation with students' learning concentration levels. The dominant impacts that emerged were attention disorders, distraction from non-learning activities, and difficulty maintaining focus for long periods. Based on these findings, it is recommended that schools and parents establish rules for gadget use and provide digital literacy education to students. This study is expected to provide input for efforts to improve the quality of learning in the SD 101 Panyabungan environment.